Distinct predictive role of collateral status on clinical outcome in variant stroke subtypes of acute large arterial occlusion. (11th December 2017) - Zhang, X.; Zhang, M.; Ding, W.; Yan, S.; Liebeskind, D. S.; Lou, M.
Abstract : Background and purpose: Clinical trials have shown that robust collateral flow has a relationship with good clinical outcome; however, different stroke subtypes were lumped together. This study explored the relationship between baseline collaterals and the onset‐to‐imaging time (OIT) and the correlation between pre‐treatment collateral status and clinical outcome amongst different subtypes. Method: Prospectively collected data from consecutive acute ischaemic stroke patients with acute middle cerebral artery occlusion who received reperfusion therapy were reviewed. The regional leptomeningeal score (20 points) was based on the scoring extent of contrast opacification in the six Alberta Stroke Program Early CT Score (ASPECTS) cortical regions (M1–6), parasagittal anterior cerebral artery territory and the basal ganglia by perfusion‐derived dynamic four‐dimensional computed tomography angiography (4D CTA). Stroke subtype was determined by the TOAST classification criteria. A 3‐months modified Rankin Scale score of 0–2 was defined as a good outcome. Results: The analysis included 158 patients: 30 (19.0%) patients had large artery atherosclerotic stroke (LAA), 87 (55.1%) cardioembolic stroke (CE) and 41 (25.9%) stroke of undetermined etiology. Baseline collateral was negatively correlated with OIT ( P = 0.0205) in the CE group after adjusting for female sex, smoking, hyperlipidemia, baseline National Institutes of Health Stroke Scale (NIHSS) and baseline mismatch ratio, but not in the LAA group. Baseline collateral showed a strong relationship with good clinical outcome after adjusting for recanalization, baseline NIHSS, age and female sex (odds ratio 1.120, confidence interval 1.013–1.238, P = 0.027) in all patients and in the CE group (odds ratio 3.223, confidence interval 1.212–8.570, P = 0.019), but not in the LAA patients. Conclusions: Based on 4D CTA, sustained good leptomeningeal collaterals may predict good outcome in CE but not in LAA patients. Moreover, the extent of collaterals was associated with OIT in the CE patients, which indicates prompt reperfusion therapy in this group of patients.